Driving Islamic work performance from transactional leadership and the mediation role of job satisfaction in sharia retails - Prasetyo, Ari; Zakik, Zakik (al-Uqud : Journal of Islamic Economics, 2024)
This research aims to analyse the influence of transactional leadership on Islamic work performance through job satisfaction at Sharia retails in Indonesia. The research method used is explanation (explanatory research). The research sample consisted of Sharia Retail employees, totalling 88 respondents. The independent variable used in the results of this study is transactional leadership. The intervening variable is job satisfaction. Dependent variable on Islamic work performance. Data collection techniques using questionnaires. The analysis technique used in this research is PLS structural equation modelling. The research results show a direct influence of transactional leadership on Islamic work performance, and transactional leadership indirectly influences Islamic work performance through job satisfaction at Sharia retail. The indirect influence of transactional leadership on Islamic work performance shows that there is a direct influence of transactional leadership on job satisfaction, and job satisfaction also influences Islamic work performance.